OCCUPATIONAL TRAINING OF THE STUDENTS OBTAINING MASTER’S DEGREE IN THE INSTRUCTIONAL FIELD IN UKRAINE: CHALLENGES, PROBLEMS, FINDINGS - Бобрицька, В. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article analysis conceptual along with organizational and scientific approaches applied to occupational training of students obtaining the Master’s degree in the instructional field at the tertiary educational establishments of Ukraine with regard to the context of the latest requirements of the state, society and instructional community; it consolidates the best practices of training of instructional experts at the National Pedagogic University named after M. P. Drahomanov; it addresses the insights into the content of educational and professional curriculum of Master’s Degree programme intended to the instructional field for the specialty referred to as 011 «Instructional/Pedagogic sciences», specialism «Educational Policy».